Pengaruh Sistem Pembayaran Non Tunai dan Potongan Harga Terhadap Kepuasan Konsumen Produk Wardah di Aster Kosmetik Malang - Pawestri Raharsiwi, Giga; Rachmi, Asminah; Nurtjahjani, Fullchis (Teewan Journal Solutions, 2025)
The rapidly growing business requires businessmen to be able to compete with competitors to maintain their business. Noticed to customer’s satisfaction can be a factor in maintaining business.Using cashless payment systems and providing price discounts can be measure of consumer’s satisfaction. The aim of this research is to analyze the cashless payment system and price discounts on consumer’s satisfaction on Wardah products at Aster Cosmetics Malang. This research uses quantitative. Data from the research was collected through a questionnarie and used a purposive sampling technique with 100 people as respondents. The data was analyzed using multiple linear regression formulae with t-test and F-test. The results of this research were that the cashless payment system had not influence on customer’s satisfaction and the price discounts had a positive influence on customer’s satisfaction. Cashless payment systems and price discounts simultaneously had an influence on customer’s satisfaction. With these results, Aster Cosmetics Malang can simplify the cashless payment systems process and extend the price discounts periode, especially for Wardah products to increase consumer’s satisfaction.